2020
DOI: 10.18332/tpc/118236
|View full text |Cite
|
Sign up to set email alerts
|

Removal of point-of-sale tobacco displays in Bogor city, Indonesia: A spatial analysis

Abstract: INTRODUCTION Indonesia contributes over 61 million smokers to global tobacco users, and the smoking prevalence is increasing among young people. In October 2017, Bogor city started the ban on tobacco displays at point-of-sale (POS), starting with modern cigarette retailers. This study aims to assess compliance with the ban and the visibility of POS with tobacco displays around educational facilities. METHODS We included 266 modern retailers surveyed throughout the city during November and December 2017. Compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Our findings are mostly consistent with previous prevalence studies of retail tobacco outlets and tobacco advertisements in Indonesia. Studies in Bali [23], East Java [24,35] and West Java [25] report that physical tobacco availability is high and that most urban residents live very close to outlets and/or advertisements. In particular, some such studies document that tobacco outlets and tobacco advertisements are common around schools [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are mostly consistent with previous prevalence studies of retail tobacco outlets and tobacco advertisements in Indonesia. Studies in Bali [23], East Java [24,35] and West Java [25] report that physical tobacco availability is high and that most urban residents live very close to outlets and/or advertisements. In particular, some such studies document that tobacco outlets and tobacco advertisements are common around schools [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Dewi et al [24] mapped 770 tobacco outlets in Banyuwangi, East Java, and found that all schools in the district had at least one outlet within 250 m. Other research has considered associations between neighbourhood socio-economic conditions and tobacco outlet characteristics. Priyono et al [25] found that 221 (83%) of 266 retailers complied with a 2017 ban on point-of-sale advertising in Bogor, West Java, and that compliance was lower in areas with higher population density and more poverty. Despite these important contributions, it is not clear how tobacco outlets are geographically distributed in Indonesia in relation to social and physical environmental characteristics, and whether specific populations are targeted by different manufacturers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this was exactly what the government of Bogor City did (i.e. adding the OTA ban and display ban into the existing SFP regulation) (Priyono et al, 2020). Another potential opportunity is to start the bans in more limited areas such as around schools.…”
Section: Discussionmentioning
confidence: 95%
“…However, national regulations to ban outdoor tobacco advertisement (OTA) and tobacco product display at the point-of-sale (POS) are nonexistent. Consequently, only a handful districts in the country (approximately 10% of districts by 2018) have piloted or implemented the bans, including Bogor City (Priyono et al, 2020). The city government initially focused on effective implementation of SFP and reached high compliance by 2014 (No Tobacco Community, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation